Comparative efficacy of topical application of tacrolimus and clotrimazole in the treatment of pityriasis versicolor: A single blind, randomised clinical trial. Issue 5 (25th January 2017) - Sepaskhah, Mozhdeh; Sadat, Maryam Sadat; Pakshir, Keyvan; Bagheri, Zahra
Summary: Background: Pityriasis versicolor (PV) is a common superficial fungal disease. Possibility of emergence of resistant strains to azoles, and difficulty in differentiation of hypopigmented PV and early vitiligo, encouraged us to evaluate the efficacy of topical tacrolimus (a calcineurin inhibitor agent with proven in vitro anti‐Malassezia effect) for PV treatment generally and its effect on PV‐induced hypopigmentation specifically. Objectives: To evaluate the efficacy of topical tacrolimus on pityriasis versicolor. Patients/Methods: Fifty PV patients were randomly allocated into two equal groups applying either topical clotrimazol or tacrolimus twice daily for 3 weeks. They were evaluated at the beginning of study, in the third and fifth weeks clinically and mycologically (direct smear). Results: Although both treatments resulted in global, clinical, and mycological cure of PV, there was no significant difference regarding the mentioned aspects of cure between tacrolimus and clotrimazole treated patients. ( P ‐value: .63, .45, and .26, respectively) Tacrolimus had no significant effect on hypopigmentation in the fifth week follow‐up. ( P ‐value: .62). Conclusions: In spite of the lack of efficacy of tacrolimus on PV‐induced hypopigmentation, the therapeutic effect on PV introduces tacrolimus as a therapeutic option for PV, especially when early vitiligo is among the differential diagnoses without concerning the aggravating effect of topical corticosteroids on PV.